ANALISA KERJA MANIFOLD ABSOLUTE PRESSURE (MAP) DAN KADAR KANDUNGAN EMISI GAS BUANG YANG DIHASILKAN PADA MOTOR BENSIN DENGAN SISTEM INJEKSI ELEKTRONIK TYPE D-EFI - Toto Sugiarto (Elektron : Jurnal Ilmiah, 2013)
This research is aim to : (1) Describe how Manifold Absolute Pressure (MAP) works at low, middle and high level rotation machine; (2) Knowing Levels of Exhaust Emission Content at low, middle and high level rotation machine. Experiment method was used for this research. EFI engine which is using MAP has been analyzed. Scan tool used to observe MAP performance and Four Gas Analyzer to detect and measure Exhaust Emission Content. From experiment found that increasing the spin machine will result in a decrease vacuum of the intake manifold. At low level rotation (750 rpm) the average of air vacuum through the MAP is 29.00 Kpa, the middle level (2000 rpm) is 26.67 Kpa, and at high speed level (5000 rpm) is 27 , 33 Kpa.